EVALUATION OF MINERAL METABOLISM IN BROILER CHICKS FED WITH CHITOSAN AND WHEY POWDER - Rakhmonov Farkhod Kholbayevich; Eshimov Dusmurat; Nuriddinova Mukhlisa Isomiddin qizi (European Science Publishing, 2025)
Great attention is paid to the development of poultry farming in our republic. Today, as in all countries, the development of poultry farming is considered an important factor in ensuring food security, and the industry plays an invaluable role in providing the population with poultry meat and egg products rich in protein and vitamins. The dry and warm climate of Uzbekistan is favorable for keeping and raising poultry.
Keywords: Chitosan, chitin, whey powder, calcium, phosphorus, broiler, poultry.